2015
DOI: 10.1186/s12879-015-1292-2
|View full text |Cite
|
Sign up to set email alerts
|

Whooping cough dynamics in Chile (1932–2010): disease temporal fluctuations across a north-south gradient

Abstract: BackgroundThe spatial-temporal dynamics of Bordetella pertussis remains as a highly interesting case in infectious disease epidemiology. Despite large-scale vaccination programs in place for over 50 years around the world, frequent outbreaks are still reported in many countries.MethodsHere, we use annual time series of pertussis incidence from the thirteen different regions of Chile (1952–2010) to study the spatial-temporal dynamics of Pertussis. The period 1975–1995 was characterized by a strong 4 year cycle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…Nine of them [25][26][27][28][29][30][31][32][33] included data from the national surveillance system SINAN (Sistema de Informação de Agravos de Notificação [System for Notifiable Diseases]); two used convenience samples of household contacts 34 or healthcare workers; 35 each used data from one 36 or ten 37 hospital clinics; and one 12 study was a population-based study. We retrieved 11 crosssectional studies, 25,26,28,29,[31][32][33][34][35]37,38 one case-control study, 13 one case series, 36 and one literature review 14 (Table 1). The pertussis-confirmed cases in the in-scope population reported by all included studies, ranged from 5.2% to 14.0% (Table 1).…”
Section: Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of them [25][26][27][28][29][30][31][32][33] included data from the national surveillance system SINAN (Sistema de Informação de Agravos de Notificação [System for Notifiable Diseases]); two used convenience samples of household contacts 34 or healthcare workers; 35 each used data from one 36 or ten 37 hospital clinics; and one 12 study was a population-based study. We retrieved 11 crosssectional studies, 25,26,28,29,[31][32][33][34][35]37,38 one case-control study, 13 one case series, 36 and one literature review 14 (Table 1). The pertussis-confirmed cases in the in-scope population reported by all included studies, ranged from 5.2% to 14.0% (Table 1).…”
Section: Brazilmentioning
confidence: 99%
“…Nine studies 25,29,[32][33][34][35][36][37][38] reported regional-level data. Of these, one was the case-series study and the others were crosssectional studies.…”
Section: Regional-level Datamentioning
confidence: 99%
“…Whooping cough is a vaccine preventable disease initially well controlled with whole cell vaccine, but due to serious complications with this vaccine, it has now been replaced with acellular vaccine. Purtussis is a public health problem worldwide and despite effective vaccinations strategies it's still endemic in many parts of the world with frequent outbreaks occurring in many countries 1 . Some have blamed the new vaccines to be less effective than the older ones and other says that new sophisticated techniques for diagnosis are responsible for rise in the disease incidence 2 .…”
Section: Introductionmentioning
confidence: 99%
“…El EHH es un efecto adverso severo que se caracteriza por la triada clínica de inicio súbito de flacidez muscular, reducida respuesta a estímulos y un cambio en la coloración de la piel (palidez o cianosis) 6 . Aunque la inmunización masiva de la población con vacunas DTwP disminuyó significativamente la ocurrencia de tos ferina 7,8 , la preocupación por los efectos adversos conllevó a que en la década de 1970 y 1980 se desarrollaran vacunas anti-pertussis acelulares (aP) compuestas por uno o más antígenos purificados (toxina pertussis, hemaglutinina filamentosa, pertactina y fimbrias). Las vacunas DTaP mostraron ser menos reactogénicas en comparación con las que contenían componentes wP y están actualmente incluidas en los programas de vacunación de muchos países desarrollados 9,10 .…”
Section: Introductionunclassified
“…Aunque las razones por las que la enfermedad está re-emergiendo son complejas y pueden variar entre países, la corta duración de la protección y el probable menor impacto de las vacunas aP sobre la infección y transmisión parecen jugar un rol importante 14 , lo que actualmente es tema de estudio y debate 15,16 . En este panorama epidemiológico, la tos ferina continúa siendo un problema en salud pública y una de las enfermedades prevenibles por vacunación más comunes en países occidentales desarrollados y en vía de desarrollo 8,17 . En Chile, la inmunización contra pertussis inició en 1955 con una vacuna combinada de wP y difteria (DP).…”
Section: Introductionunclassified